Mechanical properties and fracture behavior of high‐performance epoxy nanocomposites modified with block polymer and core–shell rubber particles. Issue 11 (4th September 2019) - Bajpai, Ankur; Wetzel, Bernd; Klingler, Andreas; Friedrich, Klaus
ABSTRACT: The mechanical properties, thermomechanical properties, and fracture mechanic properties of block‐copolymer (BCP), core–shell rubber (CSR) particles, and their hybrids in bulk epoxy/anhydride system were investigated at 23 °C. The results show that fracture toughness was increased by more than 268% for 10 wt % BCP, 200% for 12 wt % of CSR particles, and 100% for hybrid systems containing 3 wt % of each, BCP and CSR. The volume content of nanoparticles influences the final morphology and thus influences the tensile properties and fracture toughness of the modified systems. The toughening mechanisms induced by the BCP and CSR particles were identified as (1) localized plastic shear‐band yielding around the particles and (2) cavitation of the particles followed by plastic void growth in the epoxy polymer. These mechanisms were modeled using the Hsieh et al . approach and the values of G Ic of the different modified systems were calculated. Excellent agreement was found between the predicted and the experimentally measured fracture energies. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48471. Abstract : Fractured surface of hybrid epoxy nanocomposite containing BCP and CSR particles.